SYSTEMATIC TESTING METHODOLOGY TO PREDICT STRIPPING OF ASPHALT CONCRETE MIXTURE - Nabil AlKofahi; Taisir Khedaywi (Jadara Journal of Social Sciences, 2020)
The stripping of asphalt cement still the most significant reason that causes the deterioration of asphalt concrete pavement. This study aims to compare and develop a systematic method for the results of stripping tests: Texas boiling, resilient modulus, and fatigue. Three types of aggregates and two types of anti-stripping additives were used. Texas boiling test, and then Marshall specimens with (6-8%) air voids subjected to medium or high moisture conditioning were used. The stripping potential evaluated by suggesting sequence tests steps for asphalt coating retained (60-80%) visually and by the resilient modulus (MR). The visual assessment of the boiling test and the rolling test is not enough to predict stripping. The degree of saturation had a very significant effect on the resilient modulus values. The use of the resilient modulus test for Marshall specimens is a reliable test to predict stripping. For the results of less than the range; add additives and re-evaluate the stripping. For results above the range; run a fatigue test with high saturation. In general, it found that the dosage of lime needed is between 1.5 to 2.0% by weight of aggregate, where for polyamine, it was between 0.75 to 1% by weight of asphalt binder. Lime additive showed better effects on stripping potential than polyamine (liquid) additive. The proposed methodology which organized by a flow chart is a sound step-by-step and practical procedure for predicting the stripping. It could be used as a guideline to assess the water susceptibility for any aggregate type